How Dissipative Highly Non-Linear Solitary Waves Interact with Boundaries in a 1d Granular Medium - Vergara-Cofre, L (Springer Science and Business Media, LLC, 2016)
We here study the behaviour of highly non-linear solitary waves when interact with boundaries. We compare a model developed by the author with the Kubawara-Kono model. We show that this last model does not give the best results when compared with our model, proposed in Vergara (Phys. Rev. Lett. 104:118001, 2010 [1]). © Springer International Publishing Switzerland 2016.